BLOCKCHAIN: PHILOSOPHY, TECHNOLOGY, APPLICATIONS AND RISKS - V. V. Godin; A. E. Terekhova (Вестник университета)
The main ideas and properties of blockchain have been examined: architecture, models of blockchain use, in particular, decentralized autonomous organizations and applications, private blockchain – systems and blockchain – services. Blockchain infrastructure in implementation has been analyzed: reality and myths. An attention has been paid to current trends of blockchain usage in business and society in terms of opportunities, threats and risks. The areas of blockchain implementation have been presented, such as government, business, financial organizations, cryptocurrency and ICO, smart contracts and current trends of using blockchain technology.